2011
DOI: 10.1016/j.msea.2011.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclic stress and temperature on oxidation damage of a nickel-based superalloy

Abstract: Citation: KARABELA, A. ... et al., 2011 AbstractOxidation damage, combined with fatigue, is a concern for nickel-based superalloys utilised as disc rotors in high pressure compressor and turbine of aero-engines. A study has been carried out for a nickel-based alloy RR1000, which includes cyclic experiments at selected temperatures (700°C~800°C) and microscopy examination using Focused Ion Beam (FIB). The results suggest that the major mechanism of oxidation damage consists of the formation of surface oxide sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…According to studies conducted on RR1000 by Foss et al [28] and Karabela et al [20], the applied load does not influence the oxidation products, but enhances the oxidation processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to studies conducted on RR1000 by Foss et al [28] and Karabela et al [20], the applied load does not influence the oxidation products, but enhances the oxidation processes.…”
Section: Discussionmentioning
confidence: 99%
“…thermodynamic unstable oxides such as CoO and NiO at the surface and thermodynamic stable oxides such as Cr 2 O 3 , TiO 2 and Al 2 O 3 at the subsurface. Such layered oxides are usually observed in stressed and unstressed disc alloys RR1000 and ME3 [12,18,20,28], so may also form in the LSHR alloy due to the similarity in alloying composition and the comparable/equivalent test conditions. At the beginning of the fatigue loading process at elevated temperature, non-selective oxidation can occur at the specimen surface, and thereby Ni and Co oxidise rapidly and form a continuous single-phase solid solution scale due to their abundance in the alloy and the same crystal structure of NiO and CoO [18,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in oxide morphologies comes as a surprise given that most of the current literature only reports expedited kinetics. [27][28][29][30][31][32] The isotopic tracer experiments indicated that shot-peening and applied stresses have very little influence on the inward oxygen diffusion, thus eliminating enhancement due to a greater contribution from inward anionic growth. This suggests that the shot-peening and mechanical loads applied to polished samples act to influence the diffusivity of the oxidized solute species (i.e., chromium and titanium) in the parent and recrystallized alloy, [33][34][35] and this is proposed to result from defects induced from creep deformation.…”
Section: Discussionmentioning
confidence: 99%
“…The premise of this argument states that the hydrostatic stress increases the oxygen diffusivity. For example, modeling conducted by Karabela et al 27,28 described accelerated internal oxidation kinetics by first computing the hydrostatic stress gradient through crystal plasticity modeling and then the oxygen diffusion. The authors successfully rationalized the amplified oxygen penetration depths through this method; however, this analysis did not account for flux of the metallic species and the oxidation processes themselves, which inherently modify the media in which the oxygen diffuses through.…”
Section: Discussionmentioning
confidence: 99%